2020
DOI: 10.1017/jbr.2019.291
|View full text |Cite
|
Sign up to set email alerts
|

“The People Who Write to Us Are the People Who Don't Like Us”: Class, Gender, and Citizenship in the Survey of Sickness, 1943–1952

Abstract: The Second World War and the rise of social medicine in 1940s Britain reframed population health as a social problem in need of state investigation. The resulting government inquiry, the Survey of Sickness, sampled the whole adult population of England and Wales, engaging a broad and diverse cross-section in public health research for the first time. Complaints made against the Survey of Sickness reveal a complex set of relationships between different sections of the public and the British state. This article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In Daisy Payling's article about post-war social surveys, she writes about the function of complaint. 102 She cites John Clarke's observation that complaints require 'going public' and leaving a record. He describes how 'complaints represent a hinterland of anxieties, doubts, and frustrations', or as Payling puts it, 'the public articulation of private grumblings shared by many people'.…”
Section: Discussionmentioning
confidence: 99%
“…In Daisy Payling's article about post-war social surveys, she writes about the function of complaint. 102 She cites John Clarke's observation that complaints require 'going public' and leaving a record. He describes how 'complaints represent a hinterland of anxieties, doubts, and frustrations', or as Payling puts it, 'the public articulation of private grumblings shared by many people'.…”
Section: Discussionmentioning
confidence: 99%
“…As Stoler (2009) suggests, understanding the role of such materials within forms of government, and exploring the power involved in the constructions and uses of certain narratives, are important endeavours in themselves. Nonetheless, as Daisy Payling (2020) has shown in similar contexts of complaint, combining an attentiveness to the constructed nature of these sources, together with a careful reading of their embedded values and codes, can help us recuperate important accounts of waiting otherwise made marginal in the hegemonic discourses of explored here.…”
Section: Recovering Histories Of Waiting?mentioning
confidence: 91%
“…Daisy Payling has shown that 'the Second World War and the rise of social medicine encouraged the conception of whole population health as a social problem worthy of social investigation'. 213 As 'health' in general was conceptualised in increasingly social terms, with the rise of social medicine, the qualitative tools of social science and social surveys became ever more important. The use of questionnaires to understand patient experience and the social aspects of illness, in particular, was still a relatively novel phenomenon in the mid-twentieth century.…”
Section: Surveysmentioning
confidence: 99%